EDUCATION AND ITS IMPLICATIONS IN THE AGE OF COVID-19AND ITS CONSEQUENCES - Ravit, Amir (E-Journal VFU, 2025)
The global coronavirus has brought with it difficulties and challenges both economic, social and educational. Due to long lockdowns, isolation and distance learning, gaps have been created in the field of learning among Israeli students. The gaps not only in relation to the regular sub-grade but also within the classroom itself between the students were created due to subtractions, isolations, etc.The Ministry of Education has issued a budget called "Reducing COVID-19 Gaps" Basic and middle schools will receive a budget through the LPN system (managerial pedagogical flexibility) for use by the systems to reduce gaps in schools by reinforcing educational services from a pool of educational programs.Each principal must identify the difficulties and gaps in his school and submit an organized work plan aimed at reducing the educational and social gaps in the school (both in regular and special education).
Keywords: covid 19; gaps; budget; state; social; cultural; economic